Promising anticancer agents based on 8-hydroxyquinoline hydrazone copper(II) complexes - Ribeiro, Nádia; Bulut, Ipek; Sergi, Baris; Pósa, Vivien; Spengler, Gabriella; Sciortino, Giuseppe; André, Vânia; Ferreira, Liliana P.; Biver, Tarita; Ugone, Valeria; Garribba, Eugenio; Costa-Pessoa, João; et al. (Frontiers in Chemistry, 2023)
We report the synthesis and characterization of a group of benzoylhydrazones (Ln) derived from 2-carbaldehyde-8-hydroxyquinoline and benzylhydrazides containing distinct para substituents (R = H, Cl, F, CH3, OCH3, OH and NH2, for L1-7, respectively; in L8 isonicotinohydrazide was used instead of benzylhydrazide). Cu(II) complexes were prepared by reaction of each benzoylhydrazone with Cu(II) acetate. All compounds were characterized by elemental analysis and mass spectrometry as well as by FTIR, UV-visible absorption, NMR or electron paramagnetic resonance spectroscopies. Complexes isolated in the solid state (1–8) are either formulated as [Cu(HL)acetate] (with L1 and L4) or as [Cu(Ln)]3 (n = 2, 3, 5, 6, 7 and 8). Single crystal X-ray diffraction studies were done for L5 and [Cu(L5)]3, confirming the trinuclear formulation of several complexes. Proton dissociation constants, lipophilicity and solubility were determined for all free ligands by UV-Vis spectrophotometry in 30% (v/v) DMSO/H2O. Formation constants were determined for [Cu(LH)], [Cu(L)] and [Cu(LH−1)] for L = L1, L5 and L6, and also [Cu(LH−2)] for L = L6, and binding modes are proposed, [Cu(L)] predominating at physiological pH. The redox properties of complexes formed with L1, L5 and L6 are investigated by cyclic voltammetry; the formal redox potentials fall in the range of +377 to +395 mV vs. NHE. The binding of the Cu(II)-complexes to bovine serum albumin was evaluated by fluorescence spectroscopy, showing moderate-to-strong interaction and suggesting formation of a ground state complex. The interaction of L1, L3, L5 and L7, and of the corresponding complexes with calf thymus DNA was evaluated by thermal denaturation. The antiproliferative activity of all compounds was evaluated in malignant melanoma (A-375) and lung (A-549) cancer cells. The complexes show higher activity than the corresponding free ligand, and most complexes are more active than cisplatin. Compounds 1, 3, 5, and 8 were selected for additional studies: while these complexes induce reactive oxygen species and double-strand breaks in both cancer cells, their ability to induce cell-death by apoptosis varies. Within the set of compounds tested, 8 emerges as the most promising one, presenting low IC50 values, and high induction of oxidative stress and DNA damage, which eventually lead to high rates of apoptosis.